Efficacy of ricobendazole against helminthosis of cattle - E. V. Abramova; I. A. Arkhipov; V. E. Abramov; O. S. Dragunkina; N. N. Zhukova (Российский паразитологический журнал)
Efficacy of ricobendazole in 10 % solution for injection against the most helminthosis of cattle are studied. Therapeutic dosis of ricobendazole (4 mg/kg) were determined. The drug was showed 98–100% efficacy against dictyocaulosis, gastrointestinal nematodosis, monieziosis. Fasciola hepatica, Trichocephalis ovis were more resistant to action of ricobendazole.